Synchronisation in the prefrontal-striatal circuit tracks behavioural choice in a go no-go task in rats - Stubbendorff, Christine; Molano-Mazon, Manuel; Young, Andrew M.J.; Gerdjikov, Todor V. (Wiley, 2018)
Rodent striatum is involved in sensory-motor transformations and reward-related learning. Lesion studies suggest dorsolateral striatum, dorsomedial striatum, and nucleus accumbens underlie stimulus-response transformations, goal-directed behaviour and reward expectation respectively. In addition, prefrontal inputs likely control these functions. Here we set out to study how reward-driven behaviour is mediated by the coordinated activity of these structures in the intact brain. We implemented a discrimination task requiring rats to either respond or suppress responding on a lever after the presentation of auditory cues in order to obtain rewards. Single unit activity in the striatal subregions and prelimbic cortex was recorded using tetrode arrays. Striatal units showed strong onset responses to auditory cues paired with an opportunity to obtain reward. Cue onset responses in both striatum and cortex were significantly modulated by previous errors suggesting a role of these structures in maintaining appropriate motivation or action selection during ongoing behaviour. Furthermore, failure to respond to the reward-paired tones was associated with higher pre-trial coherence among striatal subregions and between cortex and striatum suggesting a task-negative corticostriatal network whose activity may be suppressed to enable processing of reward-predictive cues. Our findings highlight that coordinated activity in a distributed network including both prelimbic cortex and multiple striatal regions underlies reward-related decisions.